Short‐Term Discard Mortality Estimates for Gray Snapper in a West‐Central Florida Estuary and Adjacent Nearshore Gulf of Mexico Waters. (30th March 2016) - Flaherty‐Walia, Kerry E.; Winner, Brent L.; Tyler‐Jedlund, Amanda J.; Davis, John P.
Abstract: Gray Snapper Lutjanus griseus are fished extensively by recreational anglers in inshore estuarine habitats and in coastal and nearshore reef habitats along Florida's Gulf of Mexico coast. Although a detailed fishery assessment of Gray Snapper has never been conducted, there is a need for discard mortality estimates due to the large number of individuals captured by the recreational fishery. Our objective was to characterize discard mortality for the Gray Snapper recreational fishery in a study area that was representative of the regions in which most of the recreational fishing for this species takes place. In total, 247 Gray Snapper were caught during short‐term (48‐h) discard mortality experiments; 17 of the fish died, resulting in an overall mortality rate of 6.9%. Discard mortality was lower for fish caught from inshore waters (2/143 fish; 1.4%) than for those captured from the nearshore zone (15/104 fish; 14.4%). The water depth at the capture site and the anatomical hook location significantly influenced the probability of mortality. Individuals that were caught in shallower water and that were hooked in the lip were most likely to survive catch and release, whereas fish that were hooked in the esophagus were least likely to survive. Received July 31, 2015; accepted December 2, 2015 Published online March 30, 2016